Osmolality Selectively Offsets the Impact of Hyperthermia on Mouse Skeletal Muscle in vitro - Laitano, Orlando; Sheikh, Laila H.; Mattingly, Alex J.; Murray, Kevin O.; Ferreira, Leonardo F.; Clanton, Thomas L. (Frontiers in Physiology, 2018)
Hyperthermia and dehydration can occur during exercise in hot environments. Nevertheless, whether elevations in extracellular osmolality contributes to the increased skeletal muscle tension, sarcolemmal injury, and oxidative stress reported in warm climates remains unknown. We simulated osmotic and heat stress, in vitro, in mouse limb muscles with different fiber compositions. Extensor digitorum longus (EDL) and soleus (SOL) were dissected from 36 male C57BL6J and mounted at optimal length in tissue baths containing oxygenated buffer. Muscles were stimulated with non-fatiguing twitches for 30 min. Four experimental conditions were tested: isotonic-normothermia (285 mOsm•kg-1 and 35°C), hypertonic-normothermia (300 mOsm•kg-1 and 35°C), isotonic-hyperthermia (285 mOsm•kg-1 and 41°C), and hypertonic-hyperthermia (300 mOsm•kg-1 and 41°C). Passive tension was recorded continuously. The integrity of the sarcolemma was determined using a cell-impermeable fluorescent dye and immunoblots were used for detection of protein carbonyls. For EDL, isotonic and hypertonic-hyperthermia increased resting tension (P<0.001). Whereas isotonic-hyperthermia increased sarcolemmal injury in EDL (P<0.001), this effect was absent in hypertonic-hyperthermia. Similarly, isotonic-hyperthermia elevated protein carbonyls (P=0.018), a response not observed with hypertonic-hyperthermia. For SOL, isotonic-hyperthermia also increases resting tension (P<0.001); however, these effects were eliminated in hypertonic-hyperthermia. Unlike EDL, there were no effects of hyperthermia and/or hyperosmolality on sarcolemmal injury or protein carbonyls. Osmolality selectively modifies skeletal muscle response to hyperthermia in this model. Fast-glycolytic muscle appears particularly vulnerable to isotonic-hyperthermia, resulting in elevated muscle tension, sarcolemmal injury and protein oxidation; whereas slow-oxidative muscle exhibits increased tension but no injury or protein oxidation under the conditions and duration tested.